Pengelolaan Retribusi Sektor Pariwisata dalam Meningkatkan Pendapatan Asli Daerah di Kabupaten Katingan: Management of Tourism Sector Retribution in Increasing Regional Original Revenue in Katingan Regency - Hidayat, Noor; Rusnain, A’raf Musthafa (Pencerah Publik, 2016)
The purpose of this study was to find out how much management of retribution in the tourism sector as a supporting effort in increasing Regional Original Revenue in Katingan Regency. This study uses qualitative research. Data sources consist of primary sources (Head of Service, Secretary, Head of Division, Head of Section, Employees, and Community). Techniques for collecting data by observation, interviews, and documentation. The research results of the Katingan Regency Youth and Sports Agency are expected to be able to use as a reference in overcoming existing constraints so that PAD originating from regional retribution can increase. The approach method used in this study is a sociological juridical approach method, because it involves problems that are normatively regulated in legislation and also there are links with sociological variables, namely regarding that: The results of the study can be shown that the District Regulation No. 6 of 2009 that generally in accordance with Law No. 28 of 2009 concerning Regional Taxes and Regional Levies.